Language-related Cntnap2 gene is differentially expressed in sexually dimorphic song nuclei essential for vocal learning in songbirds - Panaitof, S. Carmen (2010)
Multiple studies, involving distinct clinical populations, implicate contactin associated protein-like 2 (CNTNAP2) in aspects of language development and performance. While CNTNAP2 is broadly distributed in developing rodent brain, it shows a striking gradient of frontal cortical enrichment in developing human brain, consistent with a role in patterning circuits that subserve higher cognition and language. To test the hypothesis that CNTNAP2 may be important for learned vocal communication in additional species, we employed in situ hybridization to characterize transcript distribution in the zebra finch, an experimentally tractable songbird for which the neural substrate of this behavior is well-established. Consistent with an important role in learned vocalization, Cntnap2 was enriched or diminished in key song control nuclei relative to adjacent brain tissue. Importantly, this punctuated expression was observed in males, but not females, in accord with the sexual dimorphism of neural circuitry and vocal learning in this species. Ongoing functional work will provide important insights into the relationship between Cntnap2 and vocal communication in songbirds and thereby clarify mechanisms at play in disorders of human cognition and language.